Hubungan antara Kemampuan Literasi Numerasi dengan Hasil Belajar Matematika Siswa Kelas Tinggi - Rosmalah Rosmalah; Sudarto Sudarto; Khaviva Hur'ainun (Universtas Negeri Makassar, 2023)
This research is a quantitative research with a symmetrical correlational type of research which aims to determine whether there is a significant relationship between numeracy literacy skills and high grade students' mathematics learning outcomes at SDN 70 Lamurukung, Tellusiattinge District, Bone Regency. Based on the results of descriptive statistical analysis, it was obtained that the numeracy literacy ability had an average of 83.77 and a percentage of 93% in the very good category and students' mathematics learning outcomes with an average of 82.67 and a percentage of 87% in the very good category. Then from the results of inferential statistical analysis obtained t count of 5.6362 and t table with a significance of 5% of 1.66462 so that t count t table. The conclusion of this study is that there is a significant relationship between numeracy literacy skills and high grade students' mathematics learning outcomes at SDN 70 Lamurukung, Tellusiattinge District, Bone Regency